An Analytical Study on Menstrual Health and Sanitation among Female Students of Dhankuta Multiple Campus - Pokhrel, Shantanu (Rupantaran: A Multidisciplinary Journal, 2025)
This study explores menstrual health and sanitation conditions of the female students inhe education faculty of Dhankuta Multiple Campus. Nepalese women experience poor menstruation health and hygiene issues. These issues impact their physical, mental, and social health. To enhance menstrual health and sanitation, it is necessary to examine the current state of the menstrual knowledge and practices among young girls. The study was conducted to identify and examine the knowledge, mensuration practice, and sanitary conditions of the respondents. The sociodemographic profile, the practice of mensuration, and care and sanitation during mensuration are analyzed in this study. The study is based on quantitative analysis and descriptive research design. A total of 60 female students were interviewed through a questionnaire, with 15 participants selected from each academic year. The data were presented in a tabular format and then analyzed. The study discovers a mixed awareness of menstruation health, with certain concerns about cultural factors and access to resources. All 60 participants reported getting information about menstruation before menarche, indicating a good level of awareness. However, the majority (65%) were restricted from certain household activities, highlighting the influence of cultural taboos, particularly among the ethnic group of Brahmin/ Chhetri and within the Hindu religious community. All participants followed sanitation practices which inline with the recommended hygiene practices, however, the study found personal preferences play an important role in menstrual management.